Agency and stewardship attitudes of chief financial officers in private companies. (2nd February 2015) - Hiebl, Martin R. W.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore the differing attitudes of salaried chief financial officers (CFOs) that can be associated with agency theory and stewardship theory. CFO attitudes are investigated because CFOs typically face additional agency conflict in their roles as overseers of the financial and accounting functions that are responsible for the production of numerical information used as a basis for incentive compensation. Design/methodology/approach – A qualitative field study of 14 large privately held Austrian manufacturing companies was conducted. The findings rely on information retrieved from 18 semi-structured interviews conducted with individuals from these companies. Findings – The findings reveal a number of contextual factors that influence stewardship and agency attitudes of salaried CFOs. CFOs, who mainly report formally to owners, perceive more control in the hands of the owners. Short-term management appointments appear to facilitate agency-like behavior, whereas the existence of owner–managers and the typical CFO's maturity in terms of age and wealth seem to nurture stewardship behavior. Research limitations/implications – Further (quantitative) research is needed to corroborate the findings in this study, which are derived from a qualitative research approach. Further research on agency and stewardship behavior should also include the view of principal with respect to agent actions, as this paper shows that principal opinion strongly affects the way agents perceive control. Practical implications – The findings suggest that the behavior of company owners can influence and change a manager's agency or stewardship attitude. Owners who desire a culture of stewardship should set long-term goals and facilitate long-term management appointments. Moreover, owners can lower a manager's perceived level of owner control by adopting an active role in management. Originality/value – This paper is the first to analyze stewardship and agency attitude of salaried CFOs in privately held companies. It, therefore, adds to the current literature on the role of the CFO, as well as to the literature on governance issues in privately held firms.